Construct Validity Analysis of the Job Crafting Scale in the Teacher Population - Rezky Eka Wardana; Andi Fitri Wahyuni (Indonesian Journal of Educational Studies, 2025)
Abstract. The purpose of this study was to test the construct validity of the Job Crafting Scale, which was adapted from Tims et al (2012). In this study, the Job Crafting Scale consists of 30 items across four categories. The sample in this study was 300 teachers from the provinces of Banten and Lampung using a non-probability sampling technique. The factor analysis method used in this study is CFA (confirmatory factor analysis) using MPlus version 7. The test results show that two items in the initial model have negative factor loadings: items 8 and 9. Although the unidimensional model is supported, the residual correlation is 57 times the threshold, so the bad items are dropped. After the analysis, the final model includes five remaining items: 3, 12, 13, 14, and 16. Still, the model satisfies the assumptions of one-dimensionality and local independence, thereby meeting the requirements of a good measuring instrument.Keywords: construct validity, job crafting scale